2022
DOI: 10.2196/26717
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile App for Wound and Symptom Surveillance After Colorectal Surgery: Protocol for a Feasibility Randomized Controlled Trial

Abstract: Background Surgical site infections (SSIs) are the most common nosocomial infection and occur in 16.3% of patients undergoing colorectal surgery at our institution (The Ottawa Hospital), the majority of which are identified after discharge from hospital. Patients who suspect having an SSI generally present to the emergency department or surgery clinic. Both options for in-person interaction are costly to the health care system and patients. A mobile app, how2trak, has proven to be beneficial for pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Many of the existing studies examining the effectiveness of a surgery information app test the design in a feasibility study without comparing it to more traditional communication methods (e.g. Semple et al, 2015;Ponder et al, 2020;Ponder et al, 2021;Joshi et al, 2022;Valk et al, 2022). By comparing the developed app to traditional patient education practices (e.g., verbal or printed information), it further allows us to understand if the developed app is a more effective communication tool.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Many of the existing studies examining the effectiveness of a surgery information app test the design in a feasibility study without comparing it to more traditional communication methods (e.g. Semple et al, 2015;Ponder et al, 2020;Ponder et al, 2021;Joshi et al, 2022;Valk et al, 2022). By comparing the developed app to traditional patient education practices (e.g., verbal or printed information), it further allows us to understand if the developed app is a more effective communication tool.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…These apps had a completion rate of the daily assessments between 21 and 84%, and had good patient satisfaction. [14][15][16][17][18][19][20][21][22][23][24]. The app of Keng et al had a 30-day readmission rate of 6% in comparison with a reported rate of 18% prior to the start of the cohort study [14].…”
Section: Monitoringmentioning
confidence: 98%
“…The effect of the app on hospital readmissions will be evaluated in a RCT [23]. The app "how2trak" is focused on surgical wound and symptom surveillance and its feasibility evaluation has not yet been completed [24].…”
Section: Monitoringmentioning
confidence: 99%
“…28 Researchers at The Ottawa Hospital plan to study how2trak, a mobile app for self-assessing signs of surgical site infection following colorectal surgery. 29 A similar study is also planned by researchers at Mount Sinai Hospital (Toronto). 30…”
Section: People Who Access the Ed Frequentlymentioning
confidence: 99%